Aromaticity of metallabenzenes and related compounds1. (21st September 2015) - Fernández, Israel; Frenking, Gernot; Merino, Gabriel
<x xml:space="preserve">Abstract</x> In this review, we focus on the aromaticity of a particular family of organometallic compounds known as metallabenzenes, which are characterized by the formal replacement of a CH group in benzene by an isolobal transition metal fragment.